Evaluating a group-based intervention to improve the safety of meat in Bodija Market, Ibadan, Nigeria - Grace, Delia; Dipeolu, M.; Olawoye, J.; Ojo, E.; Odebode, S.; Agbaje, M.; Akindana, G.; Randolph, Thomas F. (Springer, 2012)
We evaluated a group-based, participatory training intervention to improve food safety among meat processors and retailers in Bodija Market, Ibadan, Nigeria. An interactive training workshop was held for Butchers Associations’ representatives who were selected to pass on information and training to their group. Meat hygiene knowledge, attitude and practice was assessed before attending the workshop and afterwards (n = 63). It was also assessed for those who did not attend the workshop (n = 68) but were intended recipients of training through their association. Microbiological quality of meat was assessed before and after the workshop (n = 400 samples). After the workshop, participants significantly improved knowledge, attitude and practice in key food safety aspects; specifically, understanding sources of contamination and food-borne diseases, use of bleach and disinfectant and hand washing. Participants also shared information with an average of 18 other group members and improvements were seen in group members who did not attend the workshop but received training through their Butchers Association. Microbiological quality of meat sold also significantly improved after the intervention. In conclusion, participatory, group-based methods targeted at meat processors and retailers can improve meat hygiene knowledge, attitude and practice as well as the microbiological quality and hence safety of meat.